Antimicrobial Activity of Honey and Propolis from Alba County, Romania - Mihaela Laura Vică; Mirel Glevitzky; Gabriela-Alina Dumitrel; Maria Popa; Ioana Glevitzky; Cosmin Adrian Teodoru (MDPI AG, 2024)
Investigating the quality of bee products obtained across different geographical regions and analyzing their antimicrobial activity is of significant interest to various scientific disciplines. This study focuses on comparing the antimicrobial activity of honey and propolis samples from different areas of Alba County, Romania. The quality parameters of five samples of two types of bee products (honey and propolis) were assessed. Then, the samples were tested to comparatively determine their antimicrobial properties against 12 species of bacteria (Escherichia coli, Salmonella typhimurium, Salmonella enteritidis, Salmonella anatum, Salmonella choleraesuis, Pseudomonas aeruginosa, Pseudomonas fluorescens, Staphylococcus aureus, Staphylococcus epidermidis, Bacillus cereus, Bacillus subtilis, and Listeria monocytogenes) and 7 fungal strains (Candida albicans, Aspergillus niger, Aspergillus flavus, Penicillium chrysogenum, Rhizopus stolonifer, Fusarium oxysporum, and Alternaria alternata). Of the bacterial strains, the most sensitive to the action of honey samples were the two strains of Staphylococcus followed by P. fluorescens. The two strains of Pseudomonas and L. monocytogenes were the most sensitive to the activity of propolis. Of the fungal strains, F. oxysporum was the most sensitive to the actions of both honey and propolis, followed by P. chrysogenum in the case of honey samples and the two Aspergillus strains in the case of propolis. These findings indicate that bee products are rich sources of bioactive compounds exhibiting strong antimicrobial properties and significant potential for the development of new phytopharmaceutical products.